If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -13 = 85 Reorder the terms: -13 + 7x = 85 Solving -13 + 7x = 85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 7x = 85 + 13 Combine like terms: -13 + 13 = 0 0 + 7x = 85 + 13 7x = 85 + 13 Combine like terms: 85 + 13 = 98 7x = 98 Divide each side by '7'. x = 14 Simplifying x = 14
| 5(x-4)-6x=-2 | | 4x+2(x-6)=30 | | -16h=112 | | f(2)=7x^2-8 | | 3(2*6)=5x+20 | | 21-13=2(x-5) | | 7x+4x+4+7=7x+3+3x | | 3t-5t=-3-1 | | x^2+12x-6=0 | | 7x^2-13x+9=0 | | X+17+4x=-34-4x-39 | | 6.60=2.60+0.10x | | n+12=-24 | | c=40+100 | | y=2.60+0.10(26) | | n+12=24 | | 20-4x=14+2x | | 5x+6=114-10x | | -4c-3-9c=49 | | 2x-6=4x-6 | | 2x^2+18x=-3 | | -3x+8=-10 | | 4x^3-4x^2-15x+18=0 | | 5x+4=7x | | 4x+7-2x=15+4x | | 5y-2=7y+2 | | c-17=19 | | 6c^2-18c=0 | | -5y-34=2(y+2) | | 14x+12=13x+4 | | 2(x+1)-2x=2 | | 17(4c-1)-10=66c+17 |